HAP / MnFeO2 / BC catalytic material with visible light response and preparation method of HAP / MnFeO2 / BC catalytic material
By loading MnFeO2 and HAP on biochar, HAP/MnFeO2/BC photocatalytic materials are prepared, which solves the problems of low iron-based photocatalyst activity and low biochar utilization rate, and achieves efficient visible light response and material recovery, thereby improving light Catalytic properties.
Patent Information
- Application Number
- CN202411348439.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The existing iron-based photocatalysts have low catalytic activity and poor stability, low light energy utilization rate of biochar and difficult recovery, and the limited response range of hydroxyapatite to visible light, limiting its photocatalytic performance.
MnFeO2 and HAP are loaded on BC by stepwise calcination to prepare HAP/MnFeO2/BC photocatalytic materials. Through magnetic stirring, freeze-drying, calcining and grinding, the specific surface area and photoresponsiveness of the material are improved, and the specific surface area and photoresponsiveness of the material are adjusted. The dosage ratio of HAP to MnFeO2/BC is used to optimize material properties.
The visible light response performance of the material is significantly improved, the agglomeration problem of MnFeO2 is improved, the utilization rate of sunlight is improved, and the recycling rate of catalyst is improved through the recycling of magnetic materials, and the photocatalytic activity is enhanced.
Smart Images

Figure CN119215943A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a HAP / MnFeO2 / BC catalytic material with visible light response and a preparation method thereof. Background Art
[0002] There are many ways to treat organic pollution in water, such as physical adsorption, chemical oxidation and biodegradation. In recent years, photocatalytic technology has received extensive attention in the field of wastewater treatment due to its advantages such as simple operation, high treatment efficiency, good stability and high product mineralization.
[0003] At present, the application of iron-based catalysts in photocatalytic technology is mainly monometallic iron-containing compounds, such as magnetite (Fe3O4), hematite (α-Fe2O3), goethite (α-FeOOH), pyrite (FeS2) and oxyferric chloride (FeOCl), etc. However, the catalytic activity of monometallic iron-based compounds is low and the stability is poor, which is not conducive to their large-scale application. However, in the continuous exploration, various iron-based bimetallic compounds have been gradually developed, such as CuFeO2, ZnFe2O4, NiFe3O4, MnFe2O4 and MnFeO2, etc. Their narrow band gap makes them have strong absorption and response to visible light, and their chemical stability is high. They are a kind of visible light responsive photocatalytic material with application prospects. However, the specific surface area of pure phase MnFeO2 is small, it is easy to agglomerate in aqueous solution, and the recombination rate of its photogenerated electron-hole pairs is fast, so the actual photocatalytic performance is still unsatisfactory.
[0004] Biochar (BC) is a carbon material produced by calcining abundant renewable biomass resources such as leaves, fruit shells, fungus residues and straw. It has attracted widespread attention from researchers due to its advantages such as low cost, large specific surface area and rich surface functional groups. BC is usually used as a carrier of metal catalysts, such as CuFeO2 / BC, Mn / Fe-BC and nHAP@BC. In addition, BC can also be used as a reducing agent to activate persulfate and permanganate to produce highly oxidizing active substances to remove organic pollutants. BC shows good environmental advantages and is a good choice for catalytic systems, but its low light energy utilization rate and difficulty in recycling also limit its practical application.
[0005] Hydroxyapatite (HAP) is a natural mineralization of calcium apatite, which has attracted widespread attention in the fields of drug carriers, adsorbents and photocatalysts. HAP is usually synthesized from compounds containing calcium and phosphorus, and can be synthesized using different techniques such as co-precipitation, sol-gel and hydrothermal methods. HAP can also be obtained naturally from waste by-products, showing good environmental advantages. However, the band gap of HAP is about 5eV, and the light response range only occurs in the ultraviolet region. The utilization rate of sunlight is extremely low, which limits its photocatalytic performance.
[0006] In view of the problems and defects of the existing technology, it is speculated that loading MnFeO2 and HAP on BC in succession to prepare a HAP / MnFeO2 / BC photocatalytic material with visible light response is an economical and effective method in the practical application of environmental remediation technology. Summary of the invention
[0007] In view of the above situation, in order to overcome the defects of the prior art, the purpose of the present invention is to provide a HAP / MnFeO2 / BC catalytic material with visible light response and a preparation method and application thereof, so as to solve the problems raised in the above background technology. The technical solution solved by the present invention is:
[0008] A HAP / MnFeO2 / BC catalytic material with visible light response and a preparation method thereof, wherein MnFeO2 and HAP are loaded on BC in sequence by a step-by-step calcination method to obtain the HAP / MnFeO2 / BC photocatalytic material, comprising the following steps:
[0009] S1. Mn 2+ Salt, Fe 3+ Salt and straw powder were added into deionized water at the same time and then stirred with magnetic force to obtain a uniform mixture.
[0010] S2. freeze-drying the uniform mixture to obtain a solid;
[0011] S3. The solid one is transferred to the ark and placed in a high temperature combustion tube furnace, nitrogen protective gas is introduced, and solid two is calcined;
[0012] S4. The solid two was washed alternately by centrifugation with deionized water and anhydrous ethanol until neutral to obtain a solid three;
[0013] S5. The solid three was completely dried and ground with an agate mortar and sieved to obtain a solid four, namely, MnFeO2 / BC photocatalytic material;
[0014] S6. The HAP powder and solid four were simultaneously added to deionized water and shaken to obtain a uniform mixture of two;
[0015] S7. The above uniform mixed solution 2 is dried to obtain a solid 5;
[0016] S8. The solid five was transferred to the ark and placed in a high temperature combustion tube furnace and nitrogen protective gas was introduced, and calcined to obtain a solid six;
[0017] S9. The solid six was washed with deionized water and anhydrous ethanol alternately by centrifugation until neutral to obtain solid seven;
[0018] S10. After completely drying the solid 7, grinding it with an agate mortar and sieving it to obtain the solid 8, namely the HAP / MnFeO2 / BC photocatalytic material.
[0019] Further, in step S1, 30 mmol of Mn 2+ Salt and Fe 3+ The salt and 3.0 g of straw powder were simultaneously placed in 100 mL of deionized water and magnetically stirred for 2 h;
[0020] In step S2, the complete freezing temperature of the uniform mixed solution 1 is not higher than -20°C, and the freeze-drying temperature is not higher than -80°C;
[0021] In step S3, the calcination temperature of solid 1 is 750°C and the annealing time is 6 hours;
[0022] In step S6, HAP powder and MnFeO2 / BC photocatalytic material are weighed according to the configuration ratio and simultaneously placed in 20 mL of deionized water and shaken for 2 h;
[0023] In step S7, the uniform mixed solution 2 is dried in a vacuum drying oven at 80° C. for 8 h;
[0024] In step S8, the calcination temperature of the solid five is 200° C., and the annealing time is 2 h.
[0025] Furthermore, the Mn 2+ The salt is manganese acetate tetrahydrate, Fe 3+ The salt is ferric nitrate nonahydrate;
[0026] Calculated by mass, the usage ratios of HAP and MnFeO2 / BC are 5:1, 2:1, 1:1, 1:2 and 1:5.
[0027] Furthermore, the preparation process of the straw powder is as follows: the air-dried straw is cut into 2-3 cm strips, washed with distilled water and dried in a vacuum drying oven at 80°C for 8 hours, then crushed by a high-speed grinder and passed through a 60-mesh sieve to obtain the required straw powder; the straw is ginger straw.
[0028] Furthermore, the preparation process of HAP is as follows: PO4 2- The salt solution was slowly added to the Ca 2+The salt solution was magnetically stirred and the pH value of the solution was adjusted to 10. After the dropwise addition was completed, the magnetic stirring was performed for 2 hours to obtain a uniform mixed solution 3. The uniform mixed solution 3 was transferred to a high-pressure reactor and hydrothermally treated to obtain a uniform mixed solution 4. The uniform mixed solution 4 was washed by alternating centrifugation with deionized water and anhydrous ethanol until neutral and dried to obtain a solid 9, which was then ground with an agate mortar and sieved to obtain a solid 10, i.e., HAP powder.
[0029] Furthermore, PO4 2- The salt solution concentration is 0.54M, Ca 2+ The concentration of the salt solution was 0.90 M, and the molar ratio of Ca to P was maintained at 1.67;
[0030] Among them, PO4 2- The salt is diammonium phosphate, Ca 2+ The salt is calcium nitrate tetrahydrate.
[0031] Furthermore, PO4 2- The salt solution was slowly added to the Ca 2+ When using salt solution, use 5M NaOH solution to adjust the solution pH to 10.
[0032] Furthermore, the uniform mixed solution is subjected to a three-water thermal treatment at a temperature of 180° C. and a pressure of 2-3 MPa for 10 h.
[0033] Furthermore, the solid 2, the solid 6 and the uniform mixed solution 4 are washed by alternating centrifugation with deionized water and anhydrous ethanol for at least 5 times and are neutralized;
[0034] Solid three, solid seven and solid nine need to pass through a 200-mesh screen.
[0035] Compared with the traditional technology, the advantages of the present invention are:
[0036] 1. The photocatalytic material prepared by the present invention is HAP / MnFeO2 / BC, and MnFeO2 and HAP are uniformly loaded on the surface of BC successively, which greatly improves the problems of large-scale agglomeration of MnFeO2 and low utilization rate of sunlight by HAP, exposes more active sites, and improves the response performance of visible light;
[0037] 2. The HAP / MnFeO2 / BC photocatalytic material prepared by the present invention is a magnetic material, which can be effectively recovered by an external magnet after the photocatalytic treatment of wastewater reaction is completed, thereby improving the recycling rate of the catalyst;
[0038] 3. The interaction between HAP, MnFeO2 and BC in the HAP / MnFeO2 / BC photocatalytic material prepared by the present invention produces more defects and oxygen vacancies, thereby improving the photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The photocatalytic degradation efficiency of doxycycline hydrochloride by the materials obtained in Examples 1-5 and Comparative Examples 1-2 is shown;
[0040] Figure 2 The XRD spectra of the materials obtained in Example 3 and Comparative Examples 1-2 are shown. DETAILED DESCRIPTION
[0041] Here, exemplary embodiments will be described in detail, and unless otherwise indicated, the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are only examples consistent with some aspects of the present disclosure as detailed in the appended claims.
[0042] The specific implementation of the present invention is as follows:
[0043] A method for preparing a HAP / MnFeO2 / BC photocatalytic material with visible light response, characterized in that MnFeO2 and HAP are loaded on BC in sequence by a step-by-step calcination method to obtain the HAP / MnFeO2 / BC photocatalytic material.
[0044] The steps for preparing HAP / MnFeO2 / BC photocatalytic materials are summarized as follows:
[0045] First, HAP powder is prepared, then MnFeO2 / BC photocatalyst material is prepared, and finally HAP / MnFeO2 / BC photocatalyst material is prepared. Wherein, when the HAP / MnFeO2 / BC photocatalyst material is prepared, the amount ratio of HAP powder to MnFeO2 / BC photocatalyst material is 5:1, 2:1, 1:1, 1:2 and 1:5 by weight, and when it is lower than 1:5 or higher than 5:1, it is not conducive to the generation of HAP / MnFeO2 / BC photocatalyst material. Preferably, when the amount ratio of HAP powder to MnFeO2 / BC photocatalyst material is 1:1 by weight, the material with the best performance is obtained.
[0046] Example 1
[0047] A method for preparing a HAP / MnFeO2 / BC photocatalytic material with visible light response, the specific experimental steps are as follows:
[0048] At room temperature (25°C, the same below), 1000 mg of HAP powder and 200 mg of MnFeO2 / BC photocatalyst were weighed and dissolved in 20 mL of deionized water at a ratio of 5:1 by mass, and then vigorously shaken for 2 hours to obtain a uniform mixed solution. The mixed solution was dried in a vacuum drying oven at 80°C for 8 hours to obtain a solid. The solid was transferred to a corundum ark and placed in a high-temperature combustion tube furnace and maintained in a nitrogen atmosphere and annealed at 200°C for 2 hours to obtain a calcined product. The calcined product was washed alternately with deionized water and anhydrous ethanol for 5 times until neutral to obtain a washed product. The washed product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a dry product. The dry product was ground with an agate mortar and passed through a 200-mesh sieve to obtain a HAP / MnFeO2 / BC-5 photocatalyst.
[0049] Example 2
[0050] A method for preparing a HAP / MnFeO2 / BC photocatalytic material with visible light response, the specific experimental steps are as follows:
[0051] At room temperature, 400 mg of HAP powder and 200 mg of MnFeO2 / BC photocatalyst were weighed and dissolved in 20 mL of deionized water at a ratio of 2:1 by mass, and then vigorously shaken for 2 hours to obtain a uniform mixed solution. The mixed solution was dried in a vacuum drying oven at 80°C for 8 hours to obtain a solid. The solid was transferred to a corundum ark and placed in a high-temperature combustion tube furnace while maintaining a nitrogen atmosphere and annealed at 200°C for 2 hours to obtain a calcined product. The calcined product was washed alternately with deionized water and anhydrous ethanol for 5 times until neutral to obtain a washed product. The washed product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a dry product. The dry product was ground with an agate mortar and passed through a 200-mesh sieve to obtain a HAP / MnFeO2 / BC-2 photocatalyst.
[0052] Example 3
[0053] A method for preparing a HAP / MnFeO2 / BC photocatalytic material with visible light response, the specific experimental steps are as follows:
[0054] At room temperature, 200 mg of HAP powder and 200 mg of MnFeO2 / BC photocatalyst material were weighed and dissolved in 20 mL of deionized water at a ratio of 1:1 by mass, and then vigorously shaken for 2 hours to obtain a uniform mixed solution. The mixed solution was dried in a vacuum drying oven at 80°C for 8 hours to obtain a solid. The solid was transferred to a corundum ark and placed in a high-temperature combustion tube furnace while maintaining a nitrogen atmosphere and annealed at 200°C for 2 hours to obtain a calcined product. The calcined product was washed alternately with deionized water and anhydrous ethanol for 5 times until neutral to obtain a washed product. The washed product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a dried product. The dried product was ground with an agate mortar and passed through a 200-mesh sieve to obtain HAP / MnFeO2 / BC-1.
[0055] Example 4
[0056] A method for preparing a HAP / MnFeO2 / BC photocatalytic material with visible light response, the specific experimental steps are as follows:
[0057] At room temperature, 200 mg of HAP powder and 400 mg of MnFeO2 / BC photocatalyst were weighed and dissolved in 20 mL of deionized water at a ratio of 1:2 by mass, and then vigorously shaken for 2 hours to obtain a uniform mixed solution. The mixed solution was dried in a vacuum drying oven at 80°C for 8 hours to obtain a solid. The solid was transferred to a corundum ark and placed in a high-temperature combustion tube furnace while maintaining a nitrogen atmosphere and annealed at 200°C for 2 hours to obtain a calcined product. The calcined product was washed alternately with deionized water and anhydrous ethanol for 5 times until neutral to obtain a washed product. The washed product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a dry product. The dry product was ground with an agate mortar and passed through a 200-mesh sieve to obtain a HAP / MnFeO2 / BC-0.5 photocatalyst.
[0058] Example 5
[0059] A method for preparing a HAP / MnFeO2 / BC photocatalytic material with visible light response, the specific experimental steps are as follows:
[0060] At room temperature, 200 mg of HAP powder and 1000 mg of MnFeO2 / BC photocatalyst were weighed and dissolved in 20 mL of deionized water at a ratio of 1:5 by mass, and then vigorously shaken for 2 hours to obtain a uniform mixed solution. The mixed solution was dried in a vacuum drying oven at 80°C for 8 hours to obtain a solid. The solid was transferred to a corundum ark and placed in a high-temperature combustion tube furnace while maintaining a nitrogen atmosphere and annealed at 200°C for 2 hours to obtain a calcined product. The calcined product was washed alternately with deionized water and anhydrous ethanol for 5 times until neutral to obtain a washed product. The washed product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a dry product. The dry product was ground with an agate mortar and passed through a 200-mesh sieve to obtain a HAP / MnFeO2 / BC-0.2 photocatalyst.
[0061] Comparative Example 1
[0062] At room temperature, 200 mg of HAP powder was weighed and dissolved in 20 mL of deionized water at a ratio of HAP powder to MnFeO2 / BC photocatalytic material of 1:0 by mass, and then the HAP solution was obtained by vigorous shaking for 2 hours. The HAP solution was dried in a vacuum drying oven at 80°C for 8 hours to obtain a solid. The solid was transferred to a corundum ark and placed in a high-temperature combustion tube furnace while maintaining a nitrogen atmosphere and annealed at 200°C for 2 hours to obtain a calcined product. The calcined product was washed alternately with deionized water and anhydrous ethanol for 5 times until neutral to obtain a washed product. The washed product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a dried product. The dried product was ground with an agate mortar and passed through a 200-mesh sieve to obtain HAP powder, which was recorded as HAP2.
[0063] Comparative Example 2
[0064] At room temperature, 200 mg of MnFeO2 / BC photocatalyst material was weighed and dissolved in 20 mL of deionized water at a ratio of HAP powder to MnFeO2 / BC photocatalyst material of 0:1 by mass, and then vigorously shaken for 2 hours to obtain a uniform suspension. The suspension was dried in a vacuum drying oven at 80°C for 8 hours to obtain a solid. The solid was transferred to a corundum ark and placed in a high-temperature combustion tube furnace and maintained in a nitrogen atmosphere and annealed at 200°C for 2 hours to obtain a calcined product. The calcined product was washed alternately with deionized water and anhydrous ethanol for 5 times until neutral to obtain a washed product. The washed product was dried in a vacuum drying oven at 80°C for 8 hours to obtain a dry product. The dry product was ground with an agate mortar and passed through a 200-mesh sieve to obtain MnFeO2 / BC photocatalyst material, recorded as MnFeO2 / BC2.
[0065] The materials obtained in Examples 1-5 and Comparative Examples 1-2 were used to photocatalytically degrade doxycycline hydrochloride. The results are as follows: Figure 1As shown. First, the material was treated in a dark environment for 30 minutes to allow the material to reach adsorption saturation, and then a 300W xenon lamp with a wavelength of 270-780nm was used to continuously irradiate for 60 minutes for a photocatalytic degradation experiment. The results show that the self-decomposition of doxycycline hydrochloride under the irradiation of light of this range of wavelengths is very small and can be ignored. The degradation efficiency of Examples 1-5 is better than that of Comparative Example 2, which is better than the degradation efficiency of Comparative Example 1, indicating that HAP / MnFeO2 / BC has visible light response performance, and there is a synergistic effect between HAP and MnFeO2 / BC. However, the photocatalytic degradation efficiency of doxycycline hydrochloride in Examples 1-5 is not much different. Considering the preparation cost and environmental benefits, it is preferred that the preparation mass ratio of HAP powder to MnFeO2 / BC photocatalytic material is 1:1, which is the best material.
[0066] The materials obtained in Example 3 and Comparative Examples 1-2 were subjected to XRD test. The test results are as follows Figure 2 As shown. In comparative example 1, the characteristic diffraction peak in the figure can well match the characteristic diffraction peak of the standard card PDF#72-1243; in comparative example 2, it matches well with the characteristic diffraction peak of the standard card PDF#77-2359; and in Example 3, the characteristic diffraction peak can match both the standard cards PDF#72-1243 and PDF#77-2359. This indicates that the HAP / MnFeO2 / BC photocatalytic material is consistent with the dual-phase structure of HAP and MnFeO2 / BC, that is, the HAP / MnFeO2 / BC photocatalytic material is successfully prepared and relatively pure.
[0067] The above is only one of the specific implementations of the present invention, but the technical features of the present invention are not limited thereto. Any modification, equivalent replacement or improvement made within the technical concept of the present invention shall be included in the protection scope of the present invention.
Claims
1. A HAP / MnFeO2 / BC catalytic material with visible light response and a preparation method thereof, wherein MnFeO2 and HAP are loaded on BC in sequence by a step-by-step calcination method to obtain a HAP / MnFeO2 / BC photocatalytic material, characterized in that: The steps include: S1. Mn 2+ Salt, Fe 3+ Salt and straw powder were added into deionized water at the same time and then stirred with magnetic force to obtain a uniform mixture. S2. freeze-drying the uniform mixture to obtain a solid; S3. The solid one is transferred to the ark and placed in a high temperature combustion tube furnace, nitrogen protective gas is introduced, and solid two is calcined; S4. The solid two was washed alternately by centrifugation with deionized water and anhydrous ethanol until neutral to obtain solid three; S5. The solid three was completely dried and ground with an agate mortar and sieved to obtain a solid four, namely, MnFeO2 / BC photocatalytic material; S6. The HAP powder and solid four were simultaneously added to deionized water and shaken to obtain a uniform mixture of two; S7. The above uniform mixed solution 2 is dried to obtain a solid 5; S8. The solid five was transferred to the ark and placed in a high-temperature combustion tube furnace, nitrogen protective gas was introduced, and solid six was calcined; S9. The solid six was washed with deionized water and anhydrous ethanol alternately by centrifugation until neutral to obtain solid seven; S10. After completely drying the solid 7, grinding it with an agate mortar and sieving it to obtain the solid 8, namely the HAP / MnFeO2 / BC photocatalytic material.
2. The method according to claim 1, characterized in that: In step S1, 30 mmol of Mn 2+ Salt and Fe 3+ The salt and 3.0 g of straw powder were simultaneously placed in 100 mL of deionized water and magnetically stirred for 2 h; In step S2, the complete freezing temperature of the uniform mixed solution 1 is not higher than -20°C, and the freeze-drying temperature is not higher than -80°C; In step S3, the calcination temperature of solid 1 is 750°C and the annealing time is 6 hours; In step S6, HAP powder and MnFeO2 / BC photocatalytic material are weighed according to the configuration ratio and simultaneously placed in 20 mL of deionized water and shaken for 2 h; In step S7, the uniform mixed solution 2 is dried in a vacuum drying oven at 80° C. for 8 h; In step S8, the calcination temperature of the solid five is 200° C., and the annealing time is 2 h.
3. The method according to claim 1, characterized in that: The Mn 2+ The salt is manganese acetate tetrahydrate, Fe 3+ The salt is ferric nitrate nonahydrate; Calculated by mass, the usage ratios of HAP and MnFeO2 / BC are 5:1, 2:1, 1:1, 1:2 and 1:
5.
4. The method according to claim 1, characterized in that The preparation process of the straw powder is as follows: the air-dried straw is cut into 2-3 cm strips, washed with distilled water and dried in a vacuum drying oven at 80° C. for 8 hours, then crushed by a high-speed grinder and passed through a 60-mesh sieve to obtain the desired straw powder; the straw is ginger straw.
5. The method according to claim 1, characterized in that: The preparation process of HAP is as follows: PO4 2- The salt solution was slowly added to the Ca 2+ The salt solution was magnetically stirred and the pH value of the solution was adjusted to 10. After the dropwise addition was completed, the magnetic stirring was performed for 2 hours to obtain a uniform mixed solution 3. The uniform mixed solution 3 was transferred to a high-pressure reactor and hydrothermally treated to obtain a uniform mixed solution 4. The uniform mixed solution 4 was washed by alternating centrifugation with deionized water and anhydrous ethanol until neutral and dried to obtain a solid 9, which was then ground with an agate mortar and sieved to obtain a solid 10, i.e., HAP powder.
6. The method according to claim 5, characterized in that: PO4 2- The salt solution concentration is 0.54M, Ca 2+ The concentration of the salt solution was 0.90 M, and the molar ratio of Ca to P was maintained at 1.67; Among them, PO4 2- The salt is diammonium phosphate, Ca 2+ The salt is calcium nitrate tetrahydrate.
7. The method according to claim 5, characterized in that: PO4 2- The salt solution was slowly added to the Ca 2+ When using salt solution, use 5M NaOH solution to adjust the solution pH to 10.
8. The method according to claim 5, characterized in that: The conditions for the trihydrothermal treatment of the uniform mixed solution are a temperature of 180° C. and a pressure of 2-3 MPa for 10 h.
9. The method according to claim 5, characterized in that: The solid 2, the solid 6 and the uniform mixed solution 4 are washed by alternating centrifugation with deionized water and anhydrous ethanol for at least 5 times and are neutralized; Solid three, solid seven and solid nine need to pass through a 200-mesh screen.